Making out in the 'City of Gold': The coffee cart traders of Johannesburg - Rogerson, Chris (My University, 1980)
The economic, political and social hub of Southern Africa is Johannesburg, which is by far the most affluent city on the African continent. The history of this city is traditionally recorded as that of the rise of the Randlords, the growth of the mine-shafts and the transformation of raw mining camp to latterday metropolis. This picture represents, however, only one part of the story of the 'City of Gold'. The other side of Johannesburg's opulence is to be found in the life-histories and modes of existence of the people residing in the sprawling Black townships that today comprise Soweto. It is a part of their story, which constitutes the 'popular' or 'working class' history of Egoli, that is examined here. In particular, attention centres on the day-to-day struggles for survival by Blacks amid the same circumstances of poverty, unemployment and oppression that sparked in 1976 the uprising amongst the school children of Soweto.
African Studies Seminar series. Paper presented 17 June 1980
Keywords: Vending stands. South Africa. Johannesburg; Blacks. Employment. South Africa. Johannesburg